Role of Adherence in the Pathogenesis of Pseudomonas aeruginosa Lung Infection in Cystic Fibrosis Patients - Woods, Donald E. (1980)
A correlation has been demonstrated between the in vitro adherence of Pseudomonas aeruginosa to upper respiratory tract epithelium and colonization of the respiratory tract by this organism. Twenty patients with cystic fibrosis (CF) and 20 age-matched controls were examined in this study. All of the CF patients but none of the controls were colonized with P. aeruginosa at the time of study. P. aeruginosa adherence to isolated epithelial cells, as determined by an in vitro assay, was 19.1 ± 1.1 bacteria per buccal epithelial cell in the CF patients and 2.3 ± 0.3 bacteria per cell in the controls (P < 0.01). P. aeruginosa strains of the mucoid colony type adhered in significantly lower numbers to buccal epithelial cells than did strains of the rough colony type (1.8 + 0.1 versus 24.8 ± 0.9, P < 0.001). This difference might explain the common observation that the initial pseudomonas colonization of the respiratory tract of CF patients is due to organisms of the rough colony type. We have further demonstrated that increased P. aeruginosa adherence in vitro varies directly with the loss of a protease-sensitive glycoprotein, fibronectin, from the cell surface, as well as increased levels of salivary proteases in CF patients. When examined by a direct radioimmune binding assay, buccal cells from CF patients possessed only 17% of the total cell surface fibronectin present on similar cells obtained from controls. Salivary protease levels, as measured by (125)I release from an (125)I-labeled insoluble fibrin matrix, were increased about threefold in CF patients versus controls. Thus, colonization of the respiratory tract by P. aeruginosa in CF patients correlates well with buccal cell adherence of this organism; increased adherence is associated with decreased amounts of fibronectin on respiratory epithelial cell surfaces and increased levels of salivary proteases.